Digital gender divide: consumption practices and construction of digital citizenship in Colombia - Diana Esperanza Oliveros Fortiche (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales)
The digital gender divide refers to the inequality faced by women in access, use and technological domain compared to men. The characteristics of this inequality depend on the technological, social, cultural and geographical environment, among ot-her aspects. Understanding the digital gender divi-de helps to design policies that promote inclusion and equal opportunities in the digital age. This re-search contributes to this understanding from the knowledge of the relationships between digital con-sumption and the construction of Colombian digital citizenship. To achieve this objective, a non-probabilistic sample of 607 men and women bet-ween 12 and 65 years old, residents of Bogotá, was carried out, with which an exploratory factor analysis and data mining techniques such as fre-quency analysis, repeated segments and specific vocabulary were executed. The results show similar conditions by gender with respect to the digital divide, but warn about certain restrictions in terms of browsing, low political participation on the In-ternet and limited perceptions of digital citizenship in women, could widen the digital gender gap for the Colombian case.